Can someone please comment if this is right approach?

Let 'S' be Speed and 'D' be distance.

st1)Original Equation: S * (t+2) = D

New Equation(If betty's speed was 1 1/2 times as fast the trip would have taken 2 hours) => (S + 3/2 S) * 2 = D

Doesnt it mean Is 'S' was original speed new speed = s + 1 1/2 S = 5/2 S and not 1.5 S????

S * (t+2) = 5/2 S * 2

Thus 3S = St

Thus t = 3

Hence A

Is this correct? I see people write 1.5 S and not 5/2 S in the new equation .... So is my approach correct or wrong ??? PLease comment